Genomic instability in uranium miners after high radiation exposures - Streffer, Christian; Kryscio, Anna; Müller, Wolfgang-Ulrich; Kotschy-Lang, N (International Congress series, 2002)
Carcinogenesis is a multistep process with several mutations and changes of the regulation of cell proliferation. An increased genomic instability enhances the frequencies of further mutation steps. Ionising radiation increases the genomic instability in many cell generations after the exposure. This occurs in vitro and in vivo with mammalian cells. It appears that this mechanism is very important for the development of radiation late effects, especially cancer. One measure for genomic instability is the rate of micronuclei with and without centromers. This is an indication whether the micronuclei have been formed from acentric chromosome fragments or whole chromosomes. Such studies have been performed with lymphocytes of healthy persons (HP), uranium miners without (UM), and uranium miners with lung cancer (UMC). The percentage of micronuclei with centromers decreases significantly from HP to UM to UMC, whereas the absolute number of micronuclei increases but without significant difference. These data show that uranium miners have developed a genomic instability several decades after the radiation exposure. It is highest in those individuals with lung cancer. These data are the first to show that genomic instability also develops in humans in vivo.